TOKSISITAS AKUT ORAL DUA SENYAWA BISANTRAKUINON (+)-2,2’-EPISITOSKIRIN A DAN (+)-1,1’-BISLUNATIN [Oral Acute Toxicity of Two Bisanthraquinones (+)-2,2’-Epicytoskyrin A and (+)-1,1’-Bislunatin] - Praptiwi Praptiwi; Arif Nurkanto; Dewi Wulansari; Andria Agusta (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Bisanthraquinones (+) - 2,2'-epicytoskyrin A and (+) -1,1'bislunatin produced by the endophytic fungus Diaporthe sp. GNBP-10 showed potent antibacterial activity on in-vitro test and have the opportunity to become new antibiotics candidates. The aspects of safety and toxicity of drug candidates have to be examined before applying to human. This study was conducted to determine the safety aspects of the compounds through acute oral toxicity testing in mice (Mus musculus). Acute toxicity of (+) - 2,2'-epicytoskyrin A and (+) - 1,1'-bislunatin evaluated by the method of Up and Down Procedure with limit test at a dose of 2000 mg / kg. Results of acute toxicity test showed that the LD50 of (+) - 2,2'-epicytoskyrin A and (+) - 1,1'-bislunatin were of 1638.87 mg / kg and > 2000 mg / kg respectively. Administration of (+)- 2,2'-epicytoskyrin A resulted in increased miliari multifocal hepatitis, fatty degeneration and necrosis of liver cells, and the renal tubule epithelial degeneration. Administration of (+) - 1,1'-bislunatin at a dose of 2000 mg / kg resulted in multifocal accumulation of inflammatory cells in the liver and degeneration of cells in the islets of Langerhans although not resulting in death. The administration of those compounds indicated the changes in the organs, but based on the UN/ECE classification of LD50 value showed that (+) 2,2'- epicytoskyrin A and (+) -1,1'-bislunatin included as low acute toxicity substance.